ANALISIS KESULITAN BELAJAR SISWA PADA MATERI JAMUR DI KELAS X IPA SMA N 1 BATANG KUIS - Dina Alfila Lubis; Ashar Hasairin; Rengkap Rengkap (Universitas Negeri Medan, 2017)
The research aims to determine the level students’ learning difficulty in fungi subject matter and affecting factors students’ learning difficulties in class X IPA SMA Negeri 1 Batang Kuis. The population was all students X IPA SMA Negeri 1 Batang Kuis which amounted to 123 people, and the sample is all of students or total sample. This research was quantitative descriptive. Instrument of this research by using an objective test about fungi 30 questions and questionnaire which amounted to 40 items. The result show that: (1) The highest learning difficulties in fungi subject matter from cognitive aspect at level C6 (create) and the lowest at level C1 (remember); (2) The highest learning difficulties in fungi subject matter from learning indicator at indicator 5 (identifying the poisonous and edible fungi) and the lowest at indicator 1 (identifying general characteristics of fungi); (3) The highest factor affecting students’ learning difficulties in fungi subject matter is lesson and lowest factor is class.Keywords: Learning difficulties, Cognitive aspects, Learning indicators